Utilization of fish-processing waste as replacement of fish meal in aquafeed - Nurhayati A.P.D.; Novitasari E.D.; Ruswandi E.; Amin M. (BIO Web of Conferences)
Fishmeal is the most expensive component of aquaculture feed, thus finding cheaper alternative protein sources become a major challenge in aquafeed industries. This study aimed at investigating the effect of fishmeal replacement with a fish waste meal of fish processing industries on growth performances and nutrient utilization of Nile tilapia ( Oreochroms niloticus). Fish-waste of albumin-extracted Snakehead was collected, dried and grounded to produce a fine meal. The result showed that pellets produced from the fish-waste meal showed better growth, higher nutrient utilization and survival rate than the commercial pellet, p<0.05. The best Specific growth rate (SGR), feed utilization efficiency and survival rate (SR) were obtained from the tilapia receiving pellet in T3 or 60% fish-waste meal, with length and weight gain of 4.00 ± 0.11 cm and 7.99 ± 0.10 g respectively. In addition, the protein digestibility recorded from diet 3 (T3) was also significantly higher, 76.4%. However, no significant effect was observed in terms of survival rate (all 100%) and feed conversion ratio (1.44-1.53). These results suggest that the fish waste from fish processing industries can be used as fish meal replacements in aquafeed industries.